Population and development - Pavlik, Z (Acta Universitatis Carolinae. Geographica. Univerzita Karlova, 1995)
During the Paleolithic period, 10,000-100,000 people lived on the earth; their number exceeded 1 million at the beginning of the Neolithic period, reached 10 million during the Bronze Age, 100 million at the beginning of the Iron Age, 1 billion at the beginning of the 19th century, and 5.7 billion in 1995. The estimated global population will be 10 billion by the middle of the 21st century and is expected to stabilize at around 10-12 billion subsequently. Increased agricultural production helped bring about greater numbers of humanity and the advancement of society with a developing social hierarchy, although life expectancy was low at 22-28 years. In Europe, the Renaissance gradually evolved into the Industrial Revolution, and a demographic revolution accompanied this process. In some countries, population size increased more than five times. Eventually, mortality and fertility levels decreased and life expectancy increased. In Western civilization, increased individualism, secularization, compulsory school attendance, decreased agricultural population, emancipation of women, increased costs of raising children, and social and economic progress ensued. All this was preceded by 18th century conditions, when, in England, capital accumulation led to wealth on the one side and destitution on the other, giving rise to Malthus's famous theory. However, during the 19th century these social inequalities gradually evened out. After World War II, the question arose of whether the populations of other civilizations (Confucian, Japanese, Islamic, Hindu, Slavic-Orthodox, Latin American, and African) would also undergo a demographic transition and how soon. At any rate, developed country population size, as a percentage of global population, will drop from 22% to 13%, and that of Africa will increase from 12% to 26%, during the 21st century.
Keywords: fertilita; mortalita; Forecasting; výzkum; Developing Countries; Birth Rate; Research Methodology; Length Of Life; Developed Countries; Fertility; dlouhověkost; populace; Demography; Fertility Decline; Demographic Transition; Mortality; Estimation Technics; populační růst; Population Dynamics; rozvojové země; předpověď; Population Forecast; Mortality Decline; Statistics as Topic; demografie; Longevity; Population; porodnost; vyspělé země; naděje dožití; Demographic Factors; Historical Survey; statistika jako téma; Life Expectancy; populační dynamika; Population Growth; Research